Kis Géza, a „damnatio memoriae”-vel sújtott rektor - Madai, Sándor (Gerundium, 2013)
GÉZA KISS, THE RECTOR STRICKEN WITH ”DAMNATIO MEMORIAE”. Géza Kiss, a jurist, was elevated to the position of rector at the University of Debrecen when he was 36, which is an exceedingly tender age for such an honour. his internationally recognized expert of Roman law made an extraordinarily fast career when he was transferred from the academy of law at Nagyvárad to the Department of Roman Law, University of Debrecen, at the beginning of the academic year in 1914. In the academic year of 1915/1916 he was Dean of the Faculty of Law, and in 1918 he was elected Rector of the University. It was due to the events involving his activities as rector that the career of the young professor and scholar was ruined and, as a result, he was divested of his oice and even his memory was struck of the annals of the university. Not until the beginning of the 2000s was his portrait reestablished in the university rectors’ gallery.